Enthusiast Analysis For Development Department of Digital Business Diploma III in Instituto Profisional SĀO JOĀO Batista East Timor in 2024 - Guterres, Antonio; Pinto, Manuel; Gaspar, Andre Pereira; Fernandes, Luis; Francisco, Francisco; da Silva, Olivio; Tilman, Aquelino da Costa (Eduvest - Journal of Universal Studies, 2025)
The study in this study aims to examine in outline the extent to which enthusiasts for the development of digital business science at a high education level, it is known that the development of the era of industrial digitalization 4.0 has explored the world of international marketing, this is seen from the advancement of digitalization technology that has developed in a modern and sustainable manner both in the digital economy, Internet economy, Web economy, digital-based economy, new economy knowledge and innovation economy. The research method used in this study is descriptive qualitative research while to obtain the results of this research, in depth and for the benefit of proving about TL community enthusiasts regarding the development plan of the digital business department at IPJB Dili, the data collection techniques used in this study, in the form of; In-depth interviews, filling out questionnaires and questionnaires online and offline, direct observation in the field, document analysis and focus group discussion.